2009
DOI: 10.1002/jssc.200800765
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigations on relationship between Kohlrausch regulating function/inequality and moving reaction boundary in electrophoresis

Abstract: Kohlrausch regulating function (KRF) has been well defined from a moving boundary system for over 50 years. Recently, a series of theoretical and experimental studies were carried out on the concept of moving reaction boundary (MRB), including moving precipitate boundary, moving neutralization boundary and moving chelation boundaries (MCB). However, there has not been any direct evidence to show whether the KRF has validity for a MRB or not. In this paper, the KRF is derived from the equation of MRB under cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To overcome the peak broadening and to achieve better separations, AFMC was carried out between the two dimensions of the separation. AFMC is based on the micelles to transport, release, and accumulate analytes into the MDZ according to the Kohlrausch inequality (viz., the following conservation eq ) rather than the Kohlrausch regulating equation becuase a nonsteady state reaction boundary exists in the miceller collapse focusing system F normali , normali normaln = F normali italic, normalo normalu normalt + normalΔ Q normali , normalz normalo normaln normale where F is the ionic flux and Δ Q is the net increase of quantity of an ion in the nonsteady state zone per unit time.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the peak broadening and to achieve better separations, AFMC was carried out between the two dimensions of the separation. AFMC is based on the micelles to transport, release, and accumulate analytes into the MDZ according to the Kohlrausch inequality (viz., the following conservation eq ) rather than the Kohlrausch regulating equation becuase a nonsteady state reaction boundary exists in the miceller collapse focusing system F normali , normali normaln = F normali italic, normalo normalu normalt + normalΔ Q normali , normalz normalo normaln normale where F is the ionic flux and Δ Q is the net increase of quantity of an ion in the nonsteady state zone per unit time.…”
Section: Resultsmentioning
confidence: 99%
“…In pursuing the concept of analyte sweeping by a virtue of moving chelation boundary, a computer program was presented to simulate the dynamic process of an EDTA‐based sweeping of metal ions 63. However, a theoretical treatment carried out to disclose a relationship between the Kohlrausch regulating function and moving reaction boundary 64 revealed that the developed software cannot precisely compute the complex concentration and hence the stacking efficiency. Variations in the distance between an electrode and a capillary end (in vertical direction) were shown (also by computer simulation) to seriously affect repeatability 65.…”
Section: Sample Preconcentrationmentioning
confidence: 99%
“…Using the soware, they quantitatively simulated the EDTA-based sweeping of metal ion in CE. With the simulative and experimental results on MCB, Zhang et al 49 demonstrated the theoretical relationship between the Kohlrausch regulating function (the oldest function in the electrophoretic eld) 1,2 and the MRB equations. 39,40,42 In 2010, Zhang et al 50 made the further study on the MCB formed with metal ions and EDTA.…”
Section: Introductionmentioning
confidence: 99%
“…39,40,42 In 2010, Zhang et al 50 made the further study on the MCB formed with metal ions and EDTA. In their experiments, they qualitatively described the formation of MCB, moving substitution boundary (MSB) and CB, and briey observed a novel mode of MRB-based ITP in the MCB system, [48][49][50] rather than the traditional ITP. However, to the authors' knowledge, the relative general mode and theory of the MRB-based ITP have not been developed yet, the relevant theoretical deductions have not been conducted and further demonstrated by experimental proofs yet.…”
Section: Introductionmentioning
confidence: 99%